Strengthening Customer Value Development and Ethical Intent in the Salesforce: The Influence of Ethical Values Person–Organization Fit and Trust in Manager - Schwepker, Charles H., Jr. (Journal of business ethics, 2019)
This research seeks to better understand how an organization-related employee perception and job attitude may influence organizational members to ethically create customer value. Specifically, it is proposed that high person–organization fit perception, more precisely ethical values person–organization fit perception, can influence business-to-business salesperson commitment to providing superior customer value both directly and indirectly through trust in sales manager, while encouraging ethical salesforce behavior, an important aspect of communicating and delivering customer value. Results from a study of 408 business-to-business salespeople find that ethical values person–organization fit positively influences salesperson commitment to providing superior customer value, as well as trust in manager. Trust in manager directly affects commitment to customer value and mediates the relationship between ethical values person–organization fit and unethical intent. Theoretical and managerial implications are provided, as well as directions for future research.